2022
DOI: 10.1108/jqme-07-2021-0056
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of early-stage maintenance clustering

Abstract: PurposeThe purpose of this paper is to investigate the impact of early-stage maintenance clustering. Few researchers have previously studied early-stage maintenance clustering. Experience from product and service development has shown that early stages are critical to the development process, as most decisions are made during these stages. Similarly, most maintenance decisions are made during the early stages of maintenance development. Developing maintenance for clustering is expected to increase the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…A core function of this support is decision making support (Dansk Standard, 2017). In order to make decisions, some type of knowledge or information foundation is typically required (Julie K. Agergaard et al, 2022a;Kristoffer V;Sigsgaard et al, 2020). Information exists in all kinds of forms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A core function of this support is decision making support (Dansk Standard, 2017). In order to make decisions, some type of knowledge or information foundation is typically required (Julie K. Agergaard et al, 2022a;Kristoffer V;Sigsgaard et al, 2020). Information exists in all kinds of forms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liang et al [26] optimized the predictive group maintenance policy for multi-system, multi-component networks (MSMCNs) through analytical and numerical methods. Julie et al [27] suggested a clustering approach to maintenance that gained effectiveness in early development stages. Eleonora et al [28] explored roller bearing diagnostics, enhancing selection and maintenance strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The method proposed in this paper is based on Equation (27). The different reliability functions are shown in Figure 9.…”
mentioning
confidence: 99%